Simulation of mushroom-typed modified near-ballistic uni-traveling-carrier photodetector with sub-THz operational bandwidth - Shen, Yuansen; Niu, Huijuan; Chen, Qingtao; Duan, Xiaofeng; Wang, Liwen; Huang, Yongqing (Oficyna Wydawnicza Politechniki Wrocławskiej, 2025)
We report a novel mushroom-typed modified near-ballistic uni-traveling-carrier photodetector (modified NBUTC-PD) based on a drift-diffusion model which achieves high responsivity at the sub-THz regime. By well-designed active and depleted regions to form a “mushroom” type, with the optimal cliff and charge layers to make electrons transport at a “near-ballistic” speed, of order 107 cm/s, as well as the rational hybrid-doping absorber, the modified NBUTC-PD successfully achieves the decoupling between the bandwidth and responsivity characteristics. For the modified NBUTC-PD with an active area of 12.56 μm2, the simulation shows that the 3-dB bandwidth is up to 107 GHz, with a responsivity up to 0.38 A/W, at a reverse bias voltage of 1 V. The decrease in 3-dB bandwidth of the modified NBUTC-PD is analysed in detail under high-light injection conditions, which results from the energy band shift and electric field collapse.
Optica Applicata, Vol. 55, 2025, nr 1, s. 33-48
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; uni-traveling-carrier photodetector; mushroom-typed photodetector; near-ballistic transport; high responsivity; high-speed operation